Between moral responsibility and postmodern disbelief : 'postmodern ethics' in the dramatic works of harold pinter - Fernandez, Stephen Frederick (2012)
This study examines the manifestation of ‘postmodern ethics’ in the dramatic works of Harold Pinter. Zygmunt Bauman, in his examination of ethical relations in contemporary society, defines ‘postmodern ethics’ as “morality without ethical code”. However, given the complexities associated with the idea of moral responsibility, simply applying Bauman’s definition to an analysis of Pinter’s drama does not fully clarify our doubts about the representation of ‘postmodern ethics’ in his works. In order to adequately examine the exercise of moral responsibility between the characters in Pinter’s plays, there is a crucial need to consider the critical perspectives of various commentators on the notion of ‘postmodern ethics’. Moreover, the ethical relationships between the characters may indeed be influenced by other social and cultural conditions that transcend the critical frame of a fixed set of ethical principles, whether religious or secular. Throughout this study, what is meant by a fixed religious or secular ethical code is an ethical code that is universal in its application – that is, one that does not consider the specific conditions under which acts of moral responsibility or irresponsibility occur. While the actions of the characters in Pinter’s drama may be influenced by the principles of a fixed religious or secular ethical code (for example, the moral law in both its Judeo-Christian and secular renderings), such an influence, I would argue, is external to the relationships between the characters, as the motivation behind their actions is directly dependent upon the quality of their interaction with one another within a particular situation. As such, the notion of ‘postmodern ethics’ is postmodern in the sense that the assessment of the morality of a particular act would involve an examination of the specific context that contains the act, whereby any fixed religious or ethical code serves only as an external influence. For this reason, the existence of ‘postmodern ethics’ in Pinter’s drama is not directly determined by such fixed ethical codes as the Judeo-Christian moral law. Instead, the exercise of moral responsibility or irresponsibility between Pinter’s characters is conditioned by the ways in which they react to the words and actions of one another within specific contexts. Because such fixed religious or secular codes as the Judeo-Christian moral law and the Penal Code of the criminal justice system contain provisions that provide a general interpretation of what is considered moral behaviour, it is my contention that the notion of ‘postmodern ethics’ is thus capable of providing us with a specific and subjective critical approach with which to interpret and understand the morality of ethical relationships. In this way, the emphasis is not on what takes place outside of the play but what happens within it, as the exercise of moral responsibility or irresponsibility between the characters is rooted in conversation and also in its accompanying gestures that may serve either to reinforce or undermine the moral integrity of their behaviour. Consequently, the study of ‘postmodern ethics’ in Pinter’s drama brings into contention the role of responsibility (itself a construct with no absolute validity) in a postmodern world that is sceptical of institutions and absolute systems of knowledge.